PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA “MINITIM KABAR” UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Zania Ramadani; Wuli Oktiningrum (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
Weight measurement mathematics was an important material for weighing objects in everyday life. Based on the resulted of observations of students' scores on weight measurement 58% did not reach the KKM (Minimum Completeness Criteria). This study aim to (1) developing Minitim Kabar media for 2nd grade; (2) knowing the feasibility of “Minitim Kabar" media; (3) knowing the increased in cognitive learning outcomes measuring weight in Class II SD students. This research was R&D which includes 10 steps in research which include: research potentials and problems, design data, design validation, revision design, product testing, product revision, usage testing, product revision, product production. The expert tested subjects in this study were the media expert validator and the material expert validator, while the tested subjects were 6 students in the media trial and 9 students in the product trial. Data tested techniques using interviews, observation, tests, and documentation. The data analysis technique used quantitative data analysis techniques and qualitative data analysis. The resulted of this study indicate that the mini media had a high level of validity and attractiveness. The resulted of the validation of material experts were 92.3%, the resulted of the validation of media experts were 87.5%, and the proportion of student questionnaire responses was 100%. The increase in students' cognitive learning outcomes was 45.06. The N-gain test result of 0.65 was at a moderate level. Thus, the Minitim Kabar media was suitable for used as a thematic learning media to improve cognitive learning outcomes in 2nd grade on weight measurement matters.